Acute and chronic dissection of pulmonary artery: new challenges in pulmonary arterial hypertension?. (1st February 2018) - Florczyk, Michał; Wieteska, Maria; Kurzyna, Marcin; Gościniak, Piotr; Pepke‐Żaba, Joanna; Biederman, Andrzej; Torbicki, Adam
Abstract : Right ventricular failure is a leading cause of mortality in patients with pulmonary arterial hypertension (PAH). However, up to 25% of such patients die unexpectedly, without warning signs of hemodynamical decompensation. We previously documented that pulmonary artery (PA) dilatation significantly increases the risk of those deaths. Some of them may be due to dissection of PA resulting in cardiac tamponade. However, direct confirmation of this mechanism is difficult as most of such deaths occur outside hospitals. We present 4 patients with severe PAH and PA dilatation in whom PA dissection has been confirmed. Three patients had IPAH, one had PAH associated with congenital heart disease. All patients had mean pulmonary artery pressure (PAP) > 50 mmHg at diagnosis and dissection occurred late in the course of apparently well controlled disease (6 to 14 years). Several clinical elements were common to our patients ‐ high systolic PAP, long lasting PH, progressive dilatation of PA to more than 50 mm with chest pain prior to dissection. However, clinical course followed three different patterns: sudden death due to cardiac tamponade, hemopericarditis caused by blood leaking from dissected aneurysm with imminent but not immediate cardiac tamponade, or chronic asymptomatic PA dissection. Indeed, two of our patients are alive and on lung transplantation waiting list for more than 2 years now. Further research is needed to suggest optimal management strategies for patients with stable PAH but significantly dilated proximal pulmonary arteries or confirmed PA dissection depending on the clinical presentation and expected outcome.